(3EQTGO GdbGQF hGdSGeY dcJGH GdOQQ GddhGeYs - (3CMeO Hf GdWGdH eMehO Hf CYeQ COhYjTis; (3Ydj Hf eMeO Hf GdMSjf GdQHGWj, CHh GdMSf, GdeYQha HGHf HQj,J (B730 (3g` s ((3YHO GdbGOQ Hf eMeO s)
(3ChdgG (B:s
(3CeG HYO ajbhd gPG JYdjb dWja Ydi GdOQQ GddhGeY dNUJg ef cJGH JMUjd GdefGaY , hef JYdjb Ydi GdOQQ (B" (3dTjNfG YHO Gddg Hf CMeO Hf GdMGL Mei Gddg s
(3BNQgG (B:s
(3aGdMeO , Ci GdKfGA GdMSf KGHJ heSJMb ddg hMbjbI GdEdgGe ZjbGY GdNjQ ai GdbdH , hjcf ef Gdedc , hVOg GdhShI hgj EjbGY GdTQai GdbdH , hJchf ef GdTjWGf BNQ OYhGfG Cf GdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GfJgi GdeDda ef GdJCdja ai (B14 (3eMQe SfI (B1230 (3g`s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMI s
(3cJHJ HYV YHGQGJgG HGdMeQI s
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs